Mechanical behaviour of photovoltaic composite structures: Influence of geometric dimensions and material properties on the eigenfrequencies of mechanical vibrations. (December 2017) - Aßmus, M.; Naumenko, K.; Altenbach, H.
Abstract: During service and transportation, photovoltaic modules are subjected to dynamic excitation, too. From the viewpoint of structural engineering, natural frequencies of such structures should be outside of the stimulus spectrum. Knowing the location of the natural frequencies is therefore essential. The present contribution is the continuation of a recently published paper, where the considerations were stipulated on statics, while directions to optimal geometric and material parameters were revealed. In addition, we enlarge our framework and investigate the eigenbehaviour of different layouts. Thereby, we make use of an efficient and effective approach to computational solutions based on the extended layerwise theory. The results presented here constitute characteristic indexes useful in conceptual and design phase for dimensioning and material selection of photovoltaic modules. Abstract : Highlights: Framework of elastic surfaces is enlarged by terms of inertia to analyse eigenfrequencies of photovoltaic structures. Variation of geometric and material parameters is used to gain information to optimal values of significant ratios. Results constitute characteristic indexes valuable in development process of the photovoltaic module eigenbehaviour.